Ciltacabtagene autoleucel in patients with relapsed/refractory multiple myeloma: CARTITUDE‐1 (phase 2) Japanese cohort. Issue 12 (7th October 2022) - Ri, Masaki; Suzuki, Kenshi; Ishida, Tadao; Kuroda, Junya; Tsukamoto, Taku; Teshima, Takanori; Goto, Hideki; Jackson, Carolyn C.; Sun, Huabin; Pacaud, Lida; Fujikawa, Ei; Yeh, Tzu‐Min; et al.
Abstract: Chimeric antigen receptor (CAR) T cells targeting B‐cell maturation antigen have shown positive responses in patients with multiple myeloma (MM). The phase 2 portion of the CARTITUDE‐1 study of ciltacabtagene autoleucel (cilta‐cel) included a cohort of Japanese patients with relapsed/refractory MM. Following a conditioning regimen of cyclophosphamide (300 mg/m 2 ) and fludarabine (30 mg/m 2 ), patients received a single cilta‐cel infusion at a target dose of 0.75 × 10 6 (range, 0.5–1.0 × 10 6 CAR‐positive viable T cells/kg). The primary endpoint was overall response rate (ORR; defined as partial response or better) by International Myeloma Working Group criteria. A key secondary endpoint was the rate of very good partial response (VGPR) or better (defined as VGPR, complete response, stringent complete response). This first analysis was performed at 6 months after the last patient received cilta‐cel. Thirteen patients underwent apheresis, nine of whom received cilta‐cel infusion. Eight patients who received cilta‐cel at the target dose responded, yielding an ORR of 100%. Seven of eight (87.5%) patients achieved a VGPR or better. One additional patient who received a below‐target dose of cilta‐cel also achieved a best response of VGPR. MRD negativity (10 −5 threshold) was achieved in all six evaluable patients. Eight of nine (88.9%) patients who received cilta‐cel infusion experienced a grade 3 or 4 adverse event, and eight (88.9%) patients experienced cytokine release syndrome (all grade 1 or 2). No CAR‐T cell neurotoxicity was reported. A positive benefit/risk profile for cilta‐cel was established for heavily pretreated Japanese patients with relapsed or refractory MM. Abstract : CARTITUDE‐1, a phase 1b and 2 open‐label study of ciltacabtageneautoleucel (cilta‐cel) in heavily pretreated patients with relapsed/refractory multiple myeloma (RRMM), had a protocol‐specified separate Japanese cohort to characterize cilta‐cel efficacy and safety in Japanese patients. All eight of eight patients responded, yielding an overall response rate of 100% and safety was manageable and comparable to the main cohort. A positive benefit/risk profile for cilta‐cel was established for heavily pretreated Japanese patients with RRMM.